Social realities (Vol.4) - Behera,Deepak Kumar (ed.); Pfeffer,Georg (ed.) (New Delhi, 1997)
Documentation of various facets of tribal social life is very much essential before they are totally eclipsed by the rapid process of globalization of the world economy. While examining the current literature on tribal societies we notice a curious absence of scientific studies based on intensive fieldwork among a large and important section of the world population. The series Contemporary Society: Tribal Studies tries to fill in this gap and thereby attempts to remove our ignorance on many aspects of tribal social life. The ongoing series has already brought out two earlier volumes, namely (1) Structure and Process, and (2) Development Issues, Transition and Change.
Keywords: Tribal women